2020
DOI: 10.1111/jgs.16639
|View full text |Cite
|
Sign up to set email alerts
|

Physician Home Visit Patterns and Hospital Use Among Older Adults with Functional Impairments

Abstract: BACKGROUND Home‐based primary care has been associated with reductions in hospital use among homebound older adults, but population‐based studies on the general home visit patterns of primary care physicians are lacking. OBJECTIVE We examined the association between the provision of home visits by primary care physicians and subsequent use of hospital‐based care among their older adult patients with extensive functional impairments. DESIGN Population‐based retrospective cohort study. SETTING The setting was On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
(83 reference statements)
1
24
0
Order By: Relevance
“…Transitional care teams have many difficulties in addressing the need for home visits, including the lack of a supervision system and well-qualified caregivers [ 32 ]. Coordinating various departments to improve personnel training, supervision and charging systems is an effective way to promote the long-term development of home visits [ 33 ]. The needs for health lectures and online platforms were also unmet because of the existence of false information and digital gaps [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transitional care teams have many difficulties in addressing the need for home visits, including the lack of a supervision system and well-qualified caregivers [ 32 ]. Coordinating various departments to improve personnel training, supervision and charging systems is an effective way to promote the long-term development of home visits [ 33 ]. The needs for health lectures and online platforms were also unmet because of the existence of false information and digital gaps [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on primary healthcare reforms in Canada found that having regular access to a doctor reduced the risk of unmet healthcare needs (26). Encouraging individuals to have a regular primary healthcare provider seems a good way to not only reduce the most prevalent non-financial barriers to healthcare (time and information barriers) through fostering telehealth services or healthcare providers' or social service providers' visits to patients (73,74), but also to lessen financial barriers through maintaining continuity, comprehensiveness, and coordination of care (75). If regular primary healthcare providers and social service providers combine to form a primary care provider network to cater to the healthcare needs of individuals in each area of a country, it would be possible for individuals to receive timely and adequate healthcare services when they need them.…”
Section: More Policy Suggestionsmentioning
confidence: 99%
“…Although rates of physician home visits are still declining in some regions, financial incentives have driven a resurgence in these visits in the United States. 17 19 Yet, to our knowledge, there have been no population-based studies of physician home visit provision in Canada aside from 2 studies in specific subgroups (palliative care 16 and home care 8 recipients). Financial incentives for physician home visits were introduced in 2005 and 2012 in Ontario, Canada’s most populous province.…”
mentioning
confidence: 99%
“…omebound people face challenges accessing preventive, chronic and acute care, which leads to adverse health effects and an overreliance on emergency and hospital-based services. [1][2][3] Home-based primary care 4 can reduce the use of emergency department visits and hospital admissions for homebound older adults, [5][6][7][8] can provide essential information about patients' needs and home life, 9 and is perceived positively by patients, caregivers and providers. [10][11][12] For many homebound older adults, strengthening primary care at home has the twin benefits of shifting care out of hospitals and delaying the need for residential long-term care.…”
mentioning
confidence: 99%